PENGARUH PENERAPAN MEDIA GAME EDUKASI WORDWALL TERHADAP HASIL BELAJAR IPAS SISWA KELAS V UPT SDN 78 BALANG - Lastryani Jm; Amri Amal; Anisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Wordwall educational game on the science learning outcomes of fifth-grade students at UPT SDN 78 Balang. This study used a quantitative approach with a pre-experimental method through a One Group Pretest–Posttest design. The subjects of this study were 37 fifth-grade students. The data collection technique used a learning outcome test administered before and after the use of the Wordwall educational game in the learning process. The results showed that student learning outcomes improved after the use of the Wordwall educational game. The use of interactive game-based learning media can increase student motivation, engagement, and understanding of science material. Therefore, the Wordwall educational game media can be used as an effective alternative learning medium to improve elementary school student learning outcomes.